Survival of Children With Pulmonary Embolism Supported by Extracorporeal Membrane Oxygenation - Kim, John S.; Barrett, Cindy S.; Hyslop, Robert W.; Buckvold, Shannon M.; Gist, Katja M. (Frontiers in Pediatrics, 2022)
The purpose of this study was to describe the demographics and in-hospital mortality of children (<18 years) from 2007-2018 supported by Extracorporeal Membrane Oxygenation (ECMO) for a primary diagnosis of pulmonary embolism and reported to the Extracorporeal Life Support Organization database. Fifty-six patients were identified and 54 were included in this analysis. A total of 33 patients (61%) survived. No differences in demographics or ECMO details (duration, mode, support type) were found between survivors and non-survivors. When ECMO complications were compared, pulmonary bleeding occurred more frequently in non-survivors (23.8%, n=5) compared to survivors (n=0) (p=0.006).